СЕМАНТИКА СЛОВООБРАЗОВАТЕЛЬНЫХ КАТЕГОРИЙ «ОРУДИЙНОСТЬ» В РУССКОМ И УЗБЕКСКОМ ЯЗЫКАХ (Scientific journal of the Fergana State University, 2023)
The article deals with the semantics of word – formation categories “tooling” in Russian and uzbek languages.The semantic category of “tooling” is based on the universal conceptual category of the same name, directly reflects it and therefore us also universal.